AN ALGORITHM FOR APPLYING STATISTICAL METHODS IN THE IDENTIFICATION OF SUBSPECIES AND HYBRIDS OF PANTHERA PARDUS - O. Chernova; T. T. Perfiova; A. Kiladze; P. Sorokin (Теория и практика судебной экспертизы)
The study focused on the methodological aspect of applying multivariate statistics in the forensic biological analysis of mammalian hair, using samples from subspecies and hybrids of leopard.